Validity and User Satisfaction of Educational Applications for Preventive Care of Diabetic Foot Wounds: A Study in Elderly Diabetes Sufferers - Suyanto, Suyanto; Lestari Dwi Astuti, Sri (JKG (JURNAL KEPERAWATAN GLOBAL), 2024)
Background: Education on using smartphone applications among the elderly to prevent diabetic foot wounds is still limited. Especially if someone pays attention to the limitations of older people with diabetes, such as their lack of mastery in using smartphones, an educational application for preventing diabetic foot wounds, named Rawat Kaki, has been developed by considering various aspects that make it easier for older people to use. This application must be tested for validity and evaluated to obtain an overview of the satisfaction of its users. Methods: The design of this study was exploratory quantitative to see the validity of the application and respondent satisfaction using the Rawat Kaki App. The sampling technique used purposive sampling with a total sample of 140 respondents from the population of Persadia (Indonesian Diabetes Association) members at the RSUD: Surakarta City, Sragen, Salatiga, Klaten Islamic Hospital, and PrambananSleman Yogyakarta Hospital. Five diabetes experts in the medical and nursing fields conduct content validity. Furthermore, respondents tested it three times to measure their satisfaction using the EUCS (End User Computing Satisfaction) questionnaire. Results: The content validity test obtained a value of 1.02 and an alpha Cronbach reliability value of 0.765, so the Rawat Kaki application was declared feasible. Then, the data is collected through a regression test, obtaining an R-value of 0.689, which means 68.9% of application user satisfaction can be explained through the Rawat Kaki application. Conclusion: The high validity and satisfaction of respondents might be a reason to consider using this educational application.